The Relationship between Parenting and Stimulation with The Development of Toddlers Aged 1-3 Years - Desty, Inneke Clara; Abdiana, Abdiana; Mariati, Ulvi; Rahmi, Laila; Oktova, Rafika (JURNAL KEBIDANAN, 2023)
About 10 million children die and more than 200 million children develop not according to their potential triggered by parental care and stimulation. It’s estimated that about 1-5% of children under 5 years of age experience generalized developmental delays. The purpose of this study was to determine the relationship between parenting and stimulation to the development of toddlers aged 1-3 years in the working area of Koto Panjang Ikua Koto Public Health Center Padang City.  This type of research is quantitative with a Cross Sectional design, carried out in the Working Area of the Koto Panjang Ikua Koto Health Center, Padang City from September 2021 to October 2022. The sample from the study was mothers with toddlers aged 1-3 years as many as 76 people. The technique used is multistage random sampling, for data collection using the KPSP, PSQ, and Stimulation questionnaires. Univariate and bivariate data analysis using Chi-Square analysis (p<0.05). The results showed that 94.7% of children spent 24 hours with their parents, 51.3% of children had normal development, 80.3% of parents provided good stimulation and 63.2% of parents with democratic parenting styles. The results of the bivariate analysis showed that there was a relationship between parenting style and the development of children aged 1-3 years (p=0.000) and there was a relationship between stimulation and the development of children aged 1-3 years (p=0.000). Parenting parents who are democratic and good stimulation affect the optimal development of toddlers. It is hoped that the government can make policies related to parenting classes so that parents can provide good parenting and stimulation for children's growth and development.